Epigenetic aging biomarkers and occupational exposure to benzene, trichloroethylene and formaldehyde. (January 2022) - van der Laan, Lars; Cardenas, Andres; Vermeulen, Roel; Fadadu, Raj P.; Hubbard, Alan E.; Phillips, Rachael V.; Zhang, Luoping; Breeze, Charles; Hu, Wei; Wen, Cuiju; Huang, Yongshun; Tang, Xiaojiang; et al.
Highlights: Occupational exposures were associated with DNA methylation aging biomarkers. Benzene and trichloroethylene exposures increased epigenetic age acceleration. Epigenetic aging biomarkers capture impacts of environmental chemicals on health. Abstract: Epigenetic aging biomarkers are associated with increased morbidity and mortality. We evaluated if occupational exposure to three established chemical carcinogens is associated with acceleration of epigenetic aging. We studied workers in China occupationally exposed to benzene, trichloroethylene (TCE) or formaldehyde by measuring personal air exposures prior to blood collection. Unexposed controls matched by age and sex were selected from nearby factories. We measured leukocyte DNA methylation (DNAm) in peripheral white blood cells using the Infinium HumanMethylation450 BeadChip to calculate five epigenetic aging clocks and DNAmTL, a biomarker associated with leukocyte telomere length and cell replication. We tested associations between exposure intensity and epigenetic age acceleration (EAA), defined as the residuals of regressing the DNAm aging biomarker on chronological age, matching factors and potential confounders. Median differences in EAA between exposure groups were tested using a permutation test with exact p -values. Epigenetic clocks were strongly correlated with age (Spearman r  > 0.8) in all three occupational studies. There was a positive exposure-response relationship between benzene and the Skin-Blood Clock EAA biomarker: median EAA was −0.91 years in controls (n = 44), 0.78 years in workers exposed to <10 ppm (n = 41; mean benzene = 1.35 ppm; p  = 0.034 vs. controls), and 2.10 years in workers exposed to ≥10 ppm (n = 9; mean benzene = 27.3 ppm; p  = 0.019 vs. controls; p trend  = 0.0021). In the TCE study, control workers had a median Skin-Blood Clock EAA of −0.54 years (n = 71) compared to 1.63 years among workers exposed to <10 ppm of TCE (n = 27; mean TCE = 4.22 ppm; p  = 0.035). We observed no evidence of EAA associations with formaldehyde exposure (39 controls, 31 exposed). Occupational benzene and TCE exposure were associated with increased epigenetic age acceleration measured by the Skin-Blood Clock. For TCE, there was some evidence of epigenetic age acceleration for lower exposures compared to controls. Our results suggest that some chemical carcinogens may accelerate epigenetic aging.